Beyond Zakat: A Bibliometric Analysis of Poverty Research in Islamic Family Law (1990-2025) - Cipta, Hendra; Tauratiya, Tauratiya; Ismanto, Reno; Radiamoda, Anwar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
Despite the theoretical potential of Islamic family law as an integrated framework for poverty alleviation through redistributive mechanisms like inheritance (farāidh), maintenance (nafaqah), wills (wasliyyah), and waqf, global scholarship exhibits significant thematic and methodological imbalances. This study addresses the lack of a comprehensive mapping of research trends and paradigm shifts at this intersection. It asks, what are the evolutionary trends, collaboration networks, and dominant thematic foci in global research on Islamic family law and poverty from 1990 to 2025? This research is subsequently comprehensive bibliometric research. This study uses the metadata of 597 documents from Scopus, Web of Science, Dimensions, and Semantic Scholar to map evolutionary trends, collaboration networks, and high-impact theme voids within the literature. The results show a pronounced imbalance, in which one of the keywords, ‘zakat,’ accounts for almost 70% of the thematic focus to the near total exclusion of other Islamic family law redistributive mechanisms such as inheritance (farāidh), nafaqah (alimony), and will (wasliyyah). The range of disciplines is dominated by social sciences and law, while religious studies and Islamic economics are conspicuously missing. It is this narrow perspective within maqhāsid sharia that displays a disintegrated approach that does not represent the comprehensive framework and methodology that the Islamic legal tradition employs to achieve the dual objectives of poverty alleviation (hifz al maslāhah) and wealth protection through lawful means (hifz al mal). It identifies a methodological gap by showing that 82% of studies using qualitative methods do not conduct an empirical impact assessment. These findings provide an impetus for a more multidisciplinary collaborative scholarly approach centered around empirical and maqhāsid oriented frameworks to examine how synergetic all instruments of Islamic family law can be toward successful poverty alleviation.